Survey: Unconventional Categories of Chatbots that make use of Machine Learning Techniques (Journal of Information Technology and Digital World, 2023)
A growing trend in computer interaction approaches is human-computer interaction, which describes communication between a person and a computer and is known as a chatbot. A conversational agent, often known as a chatbot, is a computer program that attempts to provide responses that appear human during a conversation. Studies on several chatbot applications, are been carried out in this research on the areas of Natural Language Processing (NLP), the Natural Language understanding (NLU), and Intent recognition in recent years. There are several NLU applications in various fields, including Chatbots, search in natural language, voice-driven assistants, web- scale information extraction, legal discovery, and content summarization. Intent classification is one of the biggest challenges in NLP. Some of the chatbots classifies students requests to make them simpler to comprehend. A chatbot is an appliance of software that replicates and processes human communication to offer real-time digital assistance. Various tasks that were previously handled by human agents, like assistance to customers, medical counselling, digital commerce and issues addressing, are now being assigned to chatbots. Due to the appearance of machine learning techniques, the main step in chatbot development was defining the rules that would be used to create responses. Here are some strategies for chatbot applications and the machine-learning techniques that underpin them.
Keywords: Natural Language Processing; Machine Learning; Natural Language Understanding; Artificial intelligence; Intent Recognition Framework; Machine Learning Algorithms; Uses for various groups of chatbots; Chatbot Approaches.